2014
DOI: 10.1093/cvr/cvu167
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from human cardiac progenitor cells inhibit cardiomyocyte apoptosis and improve cardiac function after myocardial infarction

Abstract: EVs are the active component of the paracrine secretion by human CPCs. As a cell-free approach, EVs could circumvent many of the limitations of cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
611
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(648 citation statements)
references
References 30 publications
25
611
1
11
Order By: Relevance
“…Quesenberry et al (22) reported that EVs derived from either the lung or liver entered bone marrow cells in vitro and induced expression of proteins specific for the originating lung or liver tissue. Moreover, we and others have shown that miRNA delivered via exosomes represses target genes in recipient cells (5,(23)(24)(25)(26).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Quesenberry et al (22) reported that EVs derived from either the lung or liver entered bone marrow cells in vitro and induced expression of proteins specific for the originating lung or liver tissue. Moreover, we and others have shown that miRNA delivered via exosomes represses target genes in recipient cells (5,(23)(24)(25)(26).…”
mentioning
confidence: 74%
“…The vesicles exhibited a characteristic lipid bilayer membrane and were 50-100 nm in diameter, the size typically associated with exosomes. Fluorescently labeled human CPC exosomes were taken up by HL-1 myxoma atrial cells in vitro (5).…”
Section: Visualization Of Exosome Release From Cpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes secreted from mouse MSCs contained a lot of miR-22 that exerted an antiapoptotic effect on cardiomyocytes, which restored heart function and reduced infarct size in mouse MI model [54] . Exosomes isolated from human CPCs were rich in miR-210, miR-132, and miR-146a-3p, and injection of these exosomes significantly stimulated angiogenesis, suppressed apoptosis, and improved heart function in rat MI model [55] . Therefore, these findings provide persuasive evidence that stem cell-derived exosomes exert beneficial effects on the treatment of MI in animal models.…”
Section: Stem Cell-derived Exosomesmentioning
confidence: 93%
“…Previous investigations have endeavored to exploitate this mechanism using cell lysates/extracts to improve cardiac function post-MI and angiogenesis. Grossman and colleagues injected bone marrow cell extracts into periinfarct myocardium using a mouse model, and several investigators have isolated microparticles and extracellular vesicles to promote neovascularization [33][34][35] . This paracrine mechanism represents a new, alternative approach to improve post-infarct cardiac regeneration and function using stem cells.…”
Section: Figurementioning
confidence: 99%